Co-delivery of hydrophobic curcumin and hydrophilic vitamin C by nanoliposomes decorated by chitosan and gelatin - Zahra Mehrabi-Khozani; Khashayar Sarabandi; Atefe Rezaei (Carbohydrate Polymer Technologies and Applications, 2025)
In this study, the loading of vitamin C (VC) and curcumin (Cur) either separately or in combination at varying concentrations of 2, 4, and 6 mg/mL was conducted in nanoliposomal systems (NLs). The effects of coating the NLs with chitosan (single-layer: NC) and gelatin (dual-layer: NG) for the evaluation of physical stability, antioxidant activity, release, morphology, thermal stability (DSC), and chemical stability (FTIR) of the nanoparticles and loaded compounds were examined. The NLs loaded with the optimal concentration of VC (2 mg/mL) and Cur (2 mg/mL) were selected as the optimal treatment, with average particle size, PDI, zeta potential, and EE measured at approximately 70 nm, 0.4, -38 mV, 80 % (VC), and 73 % (Cur), respectively. Coating with chitosan and gelatin resulted in changes in size (from about 70 to 82 and 96 nm) and zeta potential (from about -38 to 30 and -59 mV) of the particles. DSC analysis suggested the incorporation of VC and Cur into the structures of NLs, NC, and NG. The findings of this study show the production of stable gelatin-coated nanoparticles (dual-layer) capable of preserving and releasing bioactive compounds VC and Cur in a controlled manner, with potential applications in functional beverage and food formulations.